Final report from Intergroup NCCTG 86-72-51 (Alliance): a phase III randomized clinical trial of high-dose versus low-dose radiation for adult low-grade glioma. Issue 6 (30th January 2020) - Breen, William G; Anderson, S Keith; Carrero, Xiomara W; Brown, Paul D; Ballman, Karla V; O'Neill, Brian P; Curran, Walter J; Abrams, Ross A; Laack, Nadia N; Levitt, Ralph; Galanis, Evanthia; Buckner, Jan C; et al.
Abstract: Background: The optimal radiation dose for adult supratentorial low-grade glioma is unknown. The aim of this study was to provide a final update on oncologic and cognitive outcomes of high-dose versus low-dose radiation for low-grade glioma. Methods: Between 1986 and 1994, 203 patients with supratentorial low-grade glioma were randomized (1:1) to 50.4 Gy in 28 fractions versus 64.8 Gy in 36 fractions after any degree of resection. Results: For all patients, median overall survival (OS) was 8.4 years (95% CI: 7.2–10.8). Median progression-free survival (PFS) was 5.2 years (95% CI: 4.3–6.6). Median follow-up is 17.2 years for the 33 patients still alive. High-dose radiation did not improve 15-year OS (22.4%) versus low-dose radiation (24.9%, log-rank P = 0.978) or 15-year PFS (high dose, 15.2% vs low dose, 9.5%; P = 0.7142). OS was significantly better for patients with preoperative tumor diameter <5 cm and baseline Mini-Mental State Examination (MMSE) >27 and who underwent gross total resection. PFS was improved for patients with oligodendroglioma versus astrocytoma, preoperative tumor diameter <5 cm, patients who had gross total resection, and patients with baseline MMSE >27. For patients who had normal MMSE at baseline, at 7 years only 1 patient (5%) had a clinically significant decrease in MMSE from the previous time point, with the remainder (95%) stable. None had decrease in MMSE at 10, 12, or 15 years. Conclusions: Long-term follow-up indicates no benefit to high-dose over low-dose radiation for low-grade gliomas. Cognitive function appeared to be stable after radiation as measured by MMSE.